2003
DOI: 10.1017/s0016672302006043
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate mixed inheritance models for QTL detection on porcine chromosome 6

Abstract: A series of multivariate mixed-inheritance models is fitted to the data from an outbred-line pig cross commercially used in Norway. Each model accommodates information on polygenic (co)variances between F2 individuals and their F1 parents across the five traits through incorporation of a random animal effect. Considered traits relate to meat quality and are chosen following up the results from a previous evaluation, in which a putative quantitative trait locus (QTL) was identified on chromosome six that affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
(34 reference statements)
4
15
0
Order By: Relevance
“…In the same study, QTLs from a sensory panel for subjective pork flavour and boar flavour in lean meat were described that are also located nearby the area in our study. Finally, Szyda et al (2003)[38] identified a QTL for smell intensity in a Duroc X Norwegian Landrace cross covering the area of interest. Considering the low resolution of these QTL studies, it is not possible to conclude whether they might be caused by the same genes segregating as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, QTLs from a sensory panel for subjective pork flavour and boar flavour in lean meat were described that are also located nearby the area in our study. Finally, Szyda et al (2003)[38] identified a QTL for smell intensity in a Duroc X Norwegian Landrace cross covering the area of interest. Considering the low resolution of these QTL studies, it is not possible to conclude whether they might be caused by the same genes segregating as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the multi-trait QTL mapping approaches model the genetic (co)variances by an unstructured model (Jiang and Zeng 1995;Korol et al 1998;Knott and Haley 2000;Hackett et al 2001;Lund et al 2003), which in practice limits the number of traits that can be handled. It is symptomatic that the applications of multi-trait QTL mapping under the use of unstructured (co)variance matrices never included more than just a few traits, i.e., mostly 2-5 (Calinski et al 2000;Hackett et al 2001;Szyda et al 2003;Mercadé et al 2005;Olsen et al 2005). With few traits and/or environments, the unstructured model is a possible option, although not necessarily the optimal one.…”
Section: Discussionmentioning
confidence: 99%
“…Fatness is one of the most crucial variables determining meat quality. Moreover, QTL related to fatness and meat quality traits, such as intramuscular fat content (IMF; de Koning et al, 1999de Koning et al, , 2000Gerbens et al, 1999Gerbens et al, , 2000Ovilo et al, 2000;Grindñek et al, 2001;Uleberg et al, 2005) and backfat thickness (BFT; Malek et al, 2001;Ovilo et al, 2002a;Szyda et al, 2003;Soma et al, 2011) have been identified on SSG6. Most QTL results have been integrated into Animal QTLdb (littp://www.animalgenome.org/QTLdb) by trait ontology and individual chromosomes (Hu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%